2013
DOI: 10.1089/thy.2012.0440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adjusting for the Reciprocal Relationship Between Maternal Weight and Free Thyroxine During Early Pregnancy

Abstract: for the First and Second Trimester Risk of Aneuploidy (FaSTER) Research ConsortiumBackground: Among euthyroid pregnant women in a large clinical trial, free thyroxine (FT4) measurements below the 2.5th centile were associated with a 17 lb higher weight (2.9 kg/m 2 ) than in the overall study population. We explore this relationship further. Methods: Among 9351 women with second trimester thyrotropin (TSH) measurements between 1st and 98th centiles, we examine: (i) the weight/FT4 relationship; (ii) percentages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…In 2013, we reported a reciprocal relationship between FT 4 and maternal weight among euthyroid pregnant women (15). This observation was consistent with an earlier analysis by Mannisto et al (16), who reported an inverse relationship between BMI and FT 4 in antibody-negative pregnant women.…”
Section: Resultssupporting
confidence: 89%
“…In 2013, we reported a reciprocal relationship between FT 4 and maternal weight among euthyroid pregnant women (15). This observation was consistent with an earlier analysis by Mannisto et al (16), who reported an inverse relationship between BMI and FT 4 in antibody-negative pregnant women.…”
Section: Resultssupporting
confidence: 89%
“…We performed multilevel mixed model repeated measures regression analysis for each hormone to adjust for the following potential covariates: gestational week group, maternal smoking status, age at conception, prepregnancy BMI, BMI!BMI, parity, and use of vitamins during pregnancy (15,16). Log-transformed TSH was also included as a covariate in the analysis offree thyroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has also been recently associated with low FT 4 levels, through mechanisms that are incompletely understood (33,35,48,49,50 (33). One hypothesis regarding these findings, based on the increase in T 3 seen in association with the low T 4 , is that in obesity, there is increased peripheral deiodination (52), as leptin, produced by adipose tissue, is known to stimulate T 4 to T 3 conversion (53,54).…”
Section: Causes Of Imhmentioning
confidence: 99%